Nutritional value in grains of triticale as an alternative in the food - Rodríguez-Perez, Gilberto; Cervantes-Ortiz, José Francisco; Gámez-Vázquez, Alfredo Josué; Reynaga-Franco, Felipe de Jesús; Torres-Velázquez, Jony Ramiro; Ávila-Perches, Miguel Ángel (Revista Mexicana de Ciencias Agrícolas, 2023)
The objective of this research was to identify lines of triticale (X. Triticosecale Wittmack) of value in the food industry, based on their physical and chemical properties. Twenty elite lines of spring triticale from the CIMMYT research program were established under a completely randomized experimental design with six repetitions during 2018 in Celaya, Guanajuato, Mexico, where the following variables were evaluated: WTG, HW, moisture, ashes, fat, fiber, protein, and carbohydrates. The results showed differences (p≤ 0.05) between lines, the highest values of WTG, HW and the highest percentage in fat, fiber, proteins and carbohydrates were found in lines L-18, L-17 and L-14, in addition to L-20, L-10 and L-19. The AMMI model detected significant differences (p≤ 0.05) for the lines and their interactions with physicochemical variables; the biplot graph showed that lines L-18, L-7, L-10, L-17 and L-20 expressed greater association with WTG, HW, proteins, fats, fiber and carbohydrates, which allows them to be considered in the use of the food industry for obtaining higher averages.
Keywords: X. Triticosecale Wittmack; industrial quality; physicochemical properties